Women's experience of intrapartum transfer from a Western Australian birth centre co-located to a tertiary maternity hospital - Kuliukas, L.; Duggan, Ravani; Lewis, L.; Hauck, Y. (2016)
© 2016 Kuliukas et al. Background: The aim of this Western Australian study was to describe the overall labour and birth experience of women who were transferred during the first and second stages of labour from a low risk woman-centred, midwifery-led birth centre to a co-located tertiary maternity referral hospital. Methods: Using a descriptive phenomenological design, fifteen women were interviewed up to 8weeks post birth (July to October, 2013) to explore their experience of the intrapartum transfer. Giorgi's method of analysis was used. Results: The following themes and subthemes emerged: 1) The midwife's voice with subthemes, a) The calming effect and b) Speaking up on my behalf; 2) In the zone with subthemes, a) Hanging in there and b) Post birth rationalizing; 3) Best of both worlds with subthemes a) The feeling of relief on transfer to tertiary birth suite and b) Returning back to the comfort and familiarity of the birth centre; 4) Lost sense of self; and 5) Lost birth dream with subthemes a) Narrowing of options and b) Feeling of panic. Women found the midwife's voice guided them through the transfer experience and were appreciative of continuity of care. There was a sense of disruption to expectations and disappointment in not achieving the labour and birth they had anticipated. There was however appreciation that the referral facility was nearby and experts were close at hand. The focus of care altered from woman to fetus, making women feel diminished. Women were glad to return to the familiar birth centre after the birth with the opportunity to talk through and fully understand their labour journey which helped them contextualise the transfer as one part of the whole experience. Conclusions: Findings can inform midwives of the value of a continuity of care model within a birth centre, allowing women both familiarity and peace of mind. Maternity care providers should ensure that the woman remains the focus of care after transfer and understand the significance of effective communication to ensure women are included in all care discussions.